The spinal premotor network driving scratching flexor and extensor alternation - Mingchen Yao; Akira Nagamori; Sandrina Campos Maçãs; Eiman Azim; Tatyana Sharpee; Martyn Goulding; David Golomb; Graziana Gatto (Cell Reports)
Summary: Rhythmic motor behaviors are generated by neural networks termed central pattern generators (CPGs). Although locomotor CPGs have been extensively characterized, it remains unknown how the neuronal populations composing them interact to generate adaptive rhythms in mammals. We explored the cooperation dynamics among the three main populations of ipsilaterally projecting spinal CPG neurons—V1, V2a, and V2b neurons—in scratch reflex rhythmogenesis. Individual ablation of the three neuronal populations reduced the oscillation frequency. Activation of excitatory V2a neurons enhanced the oscillation frequency, while activating inhibitory V1 neurons suppressed movement. Building on these findings, we developed a neuromechanical model made of self-oscillating flexor and extensor modules coupled via inhibition. Rhythm frequency is increased by strong intra-module inhibition and facilitation mechanisms in excitatory neurons and decreased by strong inter-module inhibition. In sum, we describe how genetically identified neuron types and the strengths of their synaptic connections drive scratch rhythmogenesis.